Foundations of Software Science and Computation Structures c - Abdulla, Parosh Aziz.; Kesner, Delia; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book constitutes the proceedings of the 28th International Conference on Foundations of Software Science and Computation Structures, FOSSACS 2025, which took place in Hamilton, Canada, during May 2025, held as part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025. The 19 papers included in these proceedings were carefully reviewed and selected from 58 submissions. They focus on foundational research in software science on theories and methods to support the analysis, integration, synthesis, transformation, and verification of programs and software systems. .
Keywords: Computer science; Mathematical logic; Data structures (Computer science).; Information theory; Computer systems; Computer science -- Mathematics; Theory of Computation; Mathematical Logic and Foundations; Data Structures and Information Theory; Computer System Implementation; Mathematics of Computing